Gambaran Pengetahuan Masyarakat terhadap Penggunaan Obat Antasida Doen di Apotek Narisa - Herman, Herman (Jurnal Farmasi Sandi Karsa, 2023)
Heartburn is a condition characterized by pain in the stomach area. Heartburn is caused by a high concentration of stomach acid. Disease with the same symptoms is gastritis but with different levels, inflammation of the gastric mucosa accompanied by damage or erosion of the mucosa. Gastritis can also occur due to infection from the bacterium Helicobacter pylori. The condition of antacid drugs does which is an over-the-counter drug that can be found anywhere is a drug that can relieve the disease, but in the service of purchasing this drug it takes people who struggle in the world of pharmacy such as pharmacists to provide information. Previous researchers have found that if you do not receive treatment that is not in accordance with medical indications it can be bad for patients, namely worsening disease conditions, decreased life expectancy, and increased health care costs. This is dangerous for buyers of these drugs if they are not right on target of the diseases and drugs they buy, so researchers are interested in seeing a picture of public knowledge about the use of Antacid Doen drugs at Narisa Pharmacy. The method used in this study is descriptive with survey techniques where data collection uses questionnaires as a measuring tool containing questions about several knowledge domains, namely Know (Know) Understand (Comprehension) Analyze (Analysis) Apply (Application) Synthesize Unite Elements into a whole then use the Gutman scale as a choice of Yes and No answers, of course prioritizing respondents' rights including inclusion and exclusion criteria. This study is a Non Probability Sampling study with an Accidental Sampling approach, namely anyone who by chance comes to buy Antacid drugs Doen met at the pharmacy, the population in this study is the surrounding community who came to buy drugs at Apotek Narisa with the number of samples based on the selection of results from the Slovin formula as many as 68 respondents. The results showed that based on the total percentage value of p score = 85.61% entered the category (76%-100%) which is can be conluded as a category of good knowledge.